2020
DOI: 10.3892/ol.2020.12262
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ten‑eleven translocation family proteins and their O‑linked β‑N‑acetylglucosaminylated forms in cancer development (Review)

Abstract: Members of the ten-eleven translocation (TET) protein family of which three mammalian TET proteins have been discovered so far, catalyze the sequential oxidation of 5-methylcytosine to 5-hydroxymethylcytosine, 5-formylcytosine, and 5-carboxylcytosine which serve an important role in embryonic development and tumor progression. O-GlcNAcylation (O-linked β-N-acetylglucosaminylation) is a reversible post-translational modification known to serve important roles in tumorigenesis and metastasis especially in hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 79 publications
1
38
0
Order By: Relevance
“…MiR-15a-5p inhibits CADM1 which stimulates Akt phosphorylation. Akt, also known as protein kinase B, is an important protein regulating cell proliferation which is over-activated in GB tissues and cells ( Figure 5 ) [ 60 ].…”
Section: Microrna In Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-15a-5p inhibits CADM1 which stimulates Akt phosphorylation. Akt, also known as protein kinase B, is an important protein regulating cell proliferation which is over-activated in GB tissues and cells ( Figure 5 ) [ 60 ].…”
Section: Microrna In Glioblastomamentioning
confidence: 99%
“…The overexpression of miR-640 promotes growth in human GB cell lines by targeting and suppressing slit guidance ligand 1 (SLIT1). Therefore, the miR-640/SLIT1 axis may be a novel potential therapeutic target for the treatment and diagnosis of GB ( Figure 5 ) [ 62 ].…”
Section: Microrna In Glioblastomamentioning
confidence: 99%
“…Another oncosuppressive microRNA is miR-126. Studies have shown that miR-126 can inhibit the proliferation of NSCLC through the suppression of EGFL7 and PTEN/PI3K/AKT signaling pathways [ 38 , 39 ]. In addition, decreased expression of miR-126 was associated with adhesion, migration, and invasion of NSCLC cells due to an increase in the Crk protein [ 40 ].…”
Section: Asbestos As a Carcinogenic Factor Of The Environmentmentioning
confidence: 99%
“…Ten-eleven translocation (TET) are important drivers of cancer initiation and progression via the regulation of epigenetic processes [ 202 ]. O-GlcNAcylation potentiates TET effects, including via DNA demethylation and histone methylation [ 202 ].…”
Section: Future Researchmentioning
confidence: 99%
“…Ten-eleven translocation (TET) are important drivers of cancer initiation and progression via the regulation of epigenetic processes [ 202 ]. O-GlcNAcylation potentiates TET effects, including via DNA demethylation and histone methylation [ 202 ]. The interactions of O-GlcNAcylated TET with the AhR/AHRR and mitochondrial function in cells of the tumour microenvironment will be important to determine, especially as this has been proposed to underpin AhR-driven active DNA demethylation and thereby epigenetic memory [ 203 ].…”
Section: Future Researchmentioning
confidence: 99%